2018
DOI: 10.1186/s12891-018-2123-6
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of vertebral refracture after kyphoplasty in patients with osteoporotic vertebral compression fractures: a study protocol for a prospective cohort study

Abstract: BackgroundPercutaneous kyphoplasty (PKP) is the first-line treatment for osteoporotic vertebral compression fractures (OVCFs) that can immediately relieve pain and allow the quick recovery of lost mobility. However, some studies reported that after PKP, the incidence of vertebral refracture, particularly adjacent vertebral fracture (AVF), was high. Our previous meta-analysis suggested that the risks for vertebral refracture and AVF did not increase after percutaneous vertebral augmentation in OVCF patients. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 35 publications
(30 reference statements)
0
27
0
Order By: Relevance
“…Some scholars believe that PVP only relieves acute pain caused by the fracture but fails to relieve the pain caused by osteoporosis. At the same time, some scholars believe that the postoperative strength of the vertebral body with compression fracture increases, changing the mechanical structure and transmission mechanism of the normal vertebral bodies, aggravating the load of the adjacent vertebral bodies, and thus increasing the risk of fracture of the adjacent vertebral bodies or causing occult trabecular bone fractures in the adjacent vertebral bodies, which will result in postoperative residual pain [ 14 ]. Yang et al performed a statistical analysis for 1316 patients treated with PVP, among which 60 complained of postoperative discomfort, with a prevalence of 4.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars believe that PVP only relieves acute pain caused by the fracture but fails to relieve the pain caused by osteoporosis. At the same time, some scholars believe that the postoperative strength of the vertebral body with compression fracture increases, changing the mechanical structure and transmission mechanism of the normal vertebral bodies, aggravating the load of the adjacent vertebral bodies, and thus increasing the risk of fracture of the adjacent vertebral bodies or causing occult trabecular bone fractures in the adjacent vertebral bodies, which will result in postoperative residual pain [ 14 ]. Yang et al performed a statistical analysis for 1316 patients treated with PVP, among which 60 complained of postoperative discomfort, with a prevalence of 4.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the increased “distance between polymethylmethacrylate and the endplate” increases the rate of refracture. [1,5,7] The intervertebral cleft is another risk factor if not properly sealed during the initial procedure. [6]…”
Section: Discussionmentioning
confidence: 99%
“…The distribution pattern for cement is classified into two types: (1) local solid lumps or (2) the trabecular/diffuse types. [5,7] In the localized solid lump pattern, the cement is confined to a small area within the anterior two-thirds of the vertebral body (e.g., particularly within the middle third of the body); it results in stress shielding, thereby increasing the risk of microfracture and progressive vertebral body height loss within the noncemented areas. For the trabecular or diffuse patterns, the cement is dispersed and fills the trabecular bone of the additional posterior one-third of the vertebral body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies had shown that it accounted for 30% -50% of the global population over the age of 50 [1]. The clinical manifestations of osteoporotic vertebral compression fractures include pain, limited physiological function, decreased quality of life, increased mortality and so on [2,3]. It will also increase the risk of adjacent vertebral c fractures in the future [4,5].…”
Section: Introductionmentioning
confidence: 99%